What and who should we focus in pediatric injury prevention – An analysis of critical pediatric trauma in a major trauma center in Hong Kong - Chon In Kuok; Winnie Kwai Yu Chan; Anthony Wai Leung Kwok (Pediatrics and Neonatology)
Background: Understanding trauma epidemiology is essential in formulating region-specific strategies for injury prevention. Our study aimed to evaluate the characteristics and clinical outcomes of critical pediatric trauma requiring intensive care in Hong Kong. Methods: A retrospective analysis was performed on pediatric patients who were injured and admitted to the pediatric intensive care unit (PICU), Queen Elizabeth Hospital, Hong Kong between 2014 and 2018. Clinical features of patients who sustained injuries before and after 2 years old were compared. Results: 141 patients were admitted to the PICU due to trauma during the study period. Most patients sustained injuries due to fall (48.2%) or road traffic injuries (34.0%), with the latter more common in older patients. Two (1.4%) patients died due to the trauma. The majority (95.0%) of the survivors had good recovery assessed by Glasgow Outcome Scale. Patients younger than 2 years old were mostly injured at home due to fall while left unattended. Children in this age group were more likely to receive interventions, including mechanical ventilation (OR 2.61; 95% CI 1.15–5.95), anti-epileptic medications (OR 2.61; 95% CI 1.17–5.83), blood transfusion (OR 5.37; 95% CI 2.29–12.60) and inotropic support (OR 4.08; 95% CI 1.31–12.70), and require longer hospitalization (PICU stay 2.5 vs. 1.5 days, p = 0.011; hospital stay 10.9 vs. 6.9 days, p = 0.012). Conclusion: Fall injuries and road traffic injuries were common etiologies of critical pediatric trauma in Hong Kong. Patients younger than 2 years old had worse clinical outcomes. Parental education on home safety and importance of close supervision should be emphasized in this age group.